Naïve models of dietary splurges: Beliefs about caloric compensation and weight change following non-habitual overconsumption. (1st September 2018) - O'Brien, Julia D.; Kahn, Rachel M.; Zenko, Zachary; Fernandez, Jessica R.; Ariely, Dan
Abstract: The mechanisms that lead to overeating and the consumption of tempting, unhealthy foods have been studied extensively, but the compensatory actions taken afterwards have not. Here we describe the naïve models individuals hold around dietary splurges (single bouts of overeating) and associated weight changes. Across six online experiments, we found that, following a hypothetical dietary splurge, participants did not plan to adequately adjust calorie consumption to account for the additional calories consumed (Studies 1 and 2), and this pattern was worse following hypothetical splurges characterized by a large amount of food consumed in a single bout (Study 3). Participants expected weight changes to happen faster than they do in reality (Study 4) and they expected that weight gained from a dietary splurge would disappear on its own without explicit compensation attempts through diet or exercise (Study 5). Similarly, participants expected that when compensation attempts were made through calorie restriction, the rate of weight loss would be faster following a dietary splurge compared to normal eating (Study 6). This research contributes novel data demonstrating an important mechanism that likely contributes to weight gain and failed weight loss attempts.